How Do Critical Thinking Ability and Critical Thinking Disposition Relate to the Mental Health of University Students? - Liu, Zhiyuan; Li, Shuangshuang; Shang, Shouwei; Ren, Xuezhu (Frontiers in Psychology, 2021)
Theories of psychotherapy suggest that human mental problems associate with deficiencies in critical thinking. However, it currently remains unclear whether both critical thinking skill and critical thinking disposition relate to individual differences in mental health. This study explored whether and how the critical thinking ability and critical thinking disposition of university students associate with individual differences in mental health in considering impulsivity that has been revealed to be closely related to both critical thinking and mental health. Regression and structural equation modeling analyses based on a Chinese university student sample (N = 314, 198 females, M age = 18.65) revealed that critical thinking skill and disposition explained a unique variance of mental health after controlling for impulsivity. Furthermore, the relationship between critical thinking and mental health was mediated by motor impulsivity (acting on the spur of the moment) and non-planning impulsivity (making decisions without careful forethought). These findings provide a preliminary account of how human critical thinking associate with mental health. Practically, developing mental health promotion programs for university students is suggested to pay special attention to cultivating their critical thinking dispositions and enhancing their control over impulsive behavior.